An introduction to computational biochemistry - Tsai, C Stan (JOHN WILEY & SONS, 2002)
The application of computational tools is rapidly becoming a standard component of molecular biology and biochemistry curricula at both the undergraduate and graduate levels. Researchers in biochemistry are required to understand, at a minimum, the basic concepts of data management and analysis using computer programs.